2022
DOI: 10.1371/journal.pone.0266097
|View full text |Cite
|
Sign up to set email alerts
|

E-scooter related injuries: Using natural language processing to rapidly search 36 million medical notes

Abstract: Background Shareable e-scooters have become popular, but injuries to riders and bystanders have not been well characterized. The goal of this study was to describe e-scooter injuries and estimate the rate of injury per e-scooter trip. Methods and findings Retrospective review of patients presenting to 180 clinics and 2 hospitals in greater Los Angeles between January 1, 2014 and May 14, 2020. Injuries were identified using a natural language processing (NLP) algorithm not previously used to identify injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Electric scooters are an increasingly common mode of transport, particularly in the urban setting, and are associated with increased risk of high energy trauma [ 1 , 2 ]. Injury rates of between 115 and 250 per million trips and fatality rates of 19 per million trips have been described [ 3 , 4 ]. The most common associated injuries are upper extremity (54%), lower extremity (47%) and head and neck (43%) [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electric scooters are an increasingly common mode of transport, particularly in the urban setting, and are associated with increased risk of high energy trauma [ 1 , 2 ]. Injury rates of between 115 and 250 per million trips and fatality rates of 19 per million trips have been described [ 3 , 4 ]. The most common associated injuries are upper extremity (54%), lower extremity (47%) and head and neck (43%) [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Injury rates of between 115 and 250 per million trips and fatality rates of 19 per million trips have been described [ 3 , 4 ]. The most common associated injuries are upper extremity (54%), lower extremity (47%) and head and neck (43%) [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Aizpuru et al found that the change in the incidence of e-scooter injuries in the USA was not significant between 2013 and 2017 [ 13 ]. Ioannides et al estimated that 115 injuries per million e-scooter trips were treated in 180 clinics and two hospitals in Los Angeles in 2014–2020 [ 14 ]. On the other hand, recent studies noted that after the launch of shared e-scooters there was a dramatic increase in e-scooter injuries – a 625% increase in Salt Lake City when comparing a control period in 2017 (i.e., before shared e-scooter programs were launched) [ 15 ] with a test period in 2018 (i.e,.…”
Section: Introductionmentioning
confidence: 99%
“…This underestimation of e-scooter RTCs was reported recently in an original study involving natural language processing conducted in Los Angeles. 25 Third, the TraumaBase register does not collect some important information, such as vehicle speed, crash cause and description, socioeconomic status of the user, health status at the time of discharge (including the place of discharge and the autonomy), or long-term health consequences.…”
Section: Limitationsmentioning
confidence: 99%